Conflict of Cross-Country Ethical Values: President of China and Prime Minister of Canada at G20 Indonesia - Dewi Bayu Pamungkas; Ida Bagus Putu Suamba (Soshum: Jurnal Sosial dan Humaniora, 2023)
The ethical conflict between the President of China and the Prime Minister of Canada at the G20 Summit in Indonesia deserves to be studied as to the causes of ethical differences between leaders. Ethical leadership, appropriate prescriptive behaviour, and promotion among staff through personal behaviour and interpersonal relationships. The focus of ethical leadership is obedience, and the content material of norms and ethical requirements varies in line with the cultural context of each country. Community members develop cognitive templates of behaviours that leaders prefer. This indicates that leaders tend to act in a manner that corresponds to their respective societal expectations of being more effective. This study uses a systematic literature review method. Ethical leadership in China is rooted in Confucian philosophy, whereas ethical leadership in Canada emphasizes performance, future orientation, and individualism. Lawrence Kohlberg on moral reasoning said that most people go through what is called the conventional cognitive level of moral development. This study provides reference material in the study of culture and cognition in ethical leadership that has not been extensively studied by researchers. This research helps people see the cultural differences that affect ethical leadership among state leaders, particularly in China and Canada. Communities can understand this difference and thus prevent conflicts in the future.